Lily HD-Zip I Transcription Factor LlHB16 Promotes Thermotolerance by Activating LlHSFA2 and LlMBF1c. (21st September 2022) - Wu, Ze; Li, Ting; Zhang, Dehua; Teng, Nianjun
Abstract: HD-Zip I transcription factors play important roles in plant development and response to abiotic stresses; however, their roles in thermotolerance are largely unknown. Through transcriptome analysis in lily ( Lilium longiflorum ), we isolated and identified a HD-Zip I gene differentially expressed at high temperatures, LlHB16, which belongs to the β2 subgroup and positively regulates thermotolerance. The expression of LlHB16 was rapidly and continuously activated by heat stress. LlHB16 protein localized to the nucleus and exhibited transactivation activity in both plant and yeast cells, and its C-terminus contributed to its transcriptional activity. Overexpressing LlHB16 in Arabidopsis and lily improved thermotolerance and activated the expression of heat-related genes in both plants, especially that of HSFA2 and MBF1c . In addition, LlHB16 overexpression in Arabidopsis also caused growth defects, delayed flowering and abscisic acid (ABA) insensitivity. Further analysis revealed that LlHB16 directly binds to the promoters of LlHSFA2 and LlMBF1c and activates their expressions. Similarly, the expression of AtHSFA2 and AtMBF1c was also elevated in LlHB16 transgenic Arabidopsis lines. Together, our findings demonstrate that LlHB16 participates in the establishment of thermotolerance involved in activating LlHSFA2 and LlMBF1c, and LlHB16 overexpression resulted in ABA insensitivity in transgenic plants, suggesting that LlHB16 links the basal heat-responsive pathway and ABA signal to collaboratively regulate thermotolerance.